2020
DOI: 10.5194/hess-24-1131-2020
|View full text |Cite
|
Sign up to set email alerts
|

Response of global evaporation to major climate modes in historical and future Coupled Model Intercomparison Project Phase 5 simulations

Abstract: Abstract. Climate extremes, such as floods and droughts, might have severe economic and societal impacts. Given the high costs associated with these events, developing early-warning systems is of high priority. Evaporation, which is driven by around 50 % of solar energy absorbed at surface of the Earth, is an important indicator of the global water budget, monsoon precipitation, drought monitoring and the hydrological cycle. Here we investigate the response of global evaporation to main modes of interannual cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 73 publications
3
20
0
Order By: Relevance
“…Significant impacts of ENSO on atmospheric aerosol loading (Figures 2a and 5) may lead to a strong response of marine productivity to ENSO. The controls of ENSO on the concentration and transportation of atmospheric dust (Figure 2a) are consistent with the influences of ENSO on global wind patterns (Dai and Wigley, 2000;Le and Bae, 2020;.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Significant impacts of ENSO on atmospheric aerosol loading (Figures 2a and 5) may lead to a strong response of marine productivity to ENSO. The controls of ENSO on the concentration and transportation of atmospheric dust (Figure 2a) are consistent with the influences of ENSO on global wind patterns (Dai and Wigley, 2000;Le and Bae, 2020;.…”
Section: Discussionsupporting
confidence: 77%
“…Following the methodology utilized in recent works (Le et al, 2021;Le and Bae, 2020), we evaluate the null hypothesis of no Granger causality between ENSO and dust activities (i.e., dust deposition rate, dust optical thickness, and emission rate of dust) by using a multivariate predictive model (see Text S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimate the probability of no Granger causality by applying a test of Granger causality (Le and Bae, 2020;Mosedale et al, 2006;Stern and Kaufmann, 2013) for the multivariate predictive model shown in equation 1.…”
Section: Text S1mentioning
confidence: 99%
“…Light isotopes are depleted in advance while heavy isotopes in raindrops are enriched [4][5][6], showing that there has been a decrease in the deuterium excess or d which equals δ 2 H − 8 × δ 18 O [7]. The evaporation and condensation are impacted by the different climate parameters [8,9], and the deuterium excess in meteoric water is also sensitive to these climate conditions [10][11][12], causing that the deuterium excess can be a useful indicator to trace the source of water vapor and assess the potential existence of the sub-cloud evaporation [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%